Analisis Potensi Pasar Tradisional Dalam Persaingan Di Era Digital Kabupaten Asahan - Yuni, Ika Darma; Lubis, Fauzi Arif; Arif, Muhammad (Jayapangus Press, 2024)
Traditional markets are markets that play an important role in advancing economic growth in Indonesia. The existence of this traditional market is very helpful, not only for the regional or central government but also for the people who depend on trading activities to make their lives prosperous, whether they are traders, buyers, agricultural workers and so on. The existence of modern markets and e-commerce makes competition between markets tight. Technological progress is something that cannot be avoided. To be able to compete with modern markets and increase traders' income, traditional markets can use the market potential of the traditional markets of Asahan Regency. Market potential is one of the supporting factors in traditional market competition in the current digital era. Utilizing and maximizing the potential that exists in this market can increase people's income and encourage people to be independent and economically independent. The aim of this research is to determine the potential of traditional markets in Asahan Regency in the digital era. The method used in this research is descriptive qualitative, by describing phenomena that occur in fact in the field. The data collection technique is by direct observation and interviews with consumers and traditional market traders. The results of this research are that the Asahan Regency traditional market has four potentials: first, land potential, second, affordable price potential, third, human resources potential of the Asahan Regency traditional market and fourth, service quality potential. With these potentials, the traditional market of Asahan Regency will be able to compete in the current digital era. And it can increase the income of traders in the traditional markets of Asahan Regency.